(untitled) (Research, Society and Development, 2023)
Third molar extraction surgery is one of the most performed surgeries by dentists and oral and maxillofacial surgeons. These are procedures that can be simple up to a context that presents a higher level of complexity, with the need for odontosection and removal of bone tissue, which tends to promote more pain, inflammation, edema, and trismus. From this point of view, corticosteroids are drugs that have been widely used to control postoperative complications, and the submucosal injection of Dexamethasone is a promising alternative. The present study is a literature review. Inclusion and exclusion criteria were established, which selected a total of 31 studies, with 54.8% (n = 17) coming from PUBMED, 32.2% (n = 10) from SCOPUS and 12.9% (n = 4) from Google Scholar. The studies were distributed between the years 2006 to 2021. In the 31 studies selected, 1817 patients were evaluated. The surgery performed and evaluated in 100% of the studies (n=31) was lower third molar exodontia. In 11 studies, the injections, in general, obtained more significant results in pain relief and edema, but there were no relevant differences between the level of action from one to the other. The current study analyzed that the submucosal application of dexamethasone can be considered an effective technique and has efficacy comparable to other forms of injection, but with the advantages of being a technique with faster local action, simple execution and less morbidity for the patient.